Synthesis of Gold Nanoparticles Using p-Aminobenzoic Acid and p-Aminosalicylic Acid as Reducing Agent - Abdul Aji; Eko Sri Kunarti; Sri Juari Santosa (Universitas Gadjah Mada, 2019)
Synthesis of gold nanoparticles (AuNPs) by reduction of HAuCl4 with p-aminobenzoic acid and p-aminosalicylic acid as a reducing agent was investigated. This work was conducted in order to determine the optimum condition of AuNPs synthesis and examine the effect of the hydroxyl group in p-aminosalicylic acid towards the size, shape, and stability of the synthesized gold nanoparticles (AuNPs). The optimum condition of the gold nanoparticles synthesis was determined by UV/Vis spectrophotometer, the shape and size of gold nanoparticles were measured by Transmission Electron Microscope (TEM). The synthesis process was started by reacting HAuCl4 and the reducing agents in an aqueous solution at 86 ºC. The initial gold concentration, reducing agents concentration and pH were varied in order to obtain the optimum condition. In the optimum condition, the results showed that p-aminosalicylic acid containing both hydroxyl and amino groups performed higher reduction ability compared to p-aminobenzoic acid that only containing an amino group. Reducing agents which have a hydroxyl group (p-aminosalicylic acid) could produce AuNPs with a smaller concentration of HAuCl4 than p-aminobenzoic acid. Gold nanoparticles that were synthesized with p-aminosalicylic acid were more stable and had a smaller particle size compared to its counterpart that is synthesized with p-aminobenzoic acid.